The use of medical imagery in hand drawn animation artworks: William Kentridge's History of the Main Complaint and other works - Murphy, Arlene (My University, 2009)
Abstract: In this research I examine two of William Kentridge’s hand-drawn animation artworks, History of the Main Complaint (1996) and Weighing and Wanting (1998), in which medical imagery is utilized to investigate forms of self narration. In these animation artworks Kentridge’s choice of medical imagery focuses particularly on technologies used to reflect the interior of the body, such as X-rays, sonar scans and Magnetic Resonance imaging (MRI) scans. He correlates such forms of looking into the human body with ideas of excavating history and revealing personal introspection. Medical imagery is thus used as a form of metaphoric expression of autobiography as the scrutinizing of the interior of the body comes to represent a probing into repressed memories. Kentridge has developed a particular method of animation in which he shapes single charcoal drawings into sequences on film. His technique of drawing images over previously erased ones is strongly associative of memory function and the imagery he uses exhibits highly personal reflections on history and memory related to post-apartheid South Africa. Drawing on ideas about the self from various disciplines, I formulate a workable definition that will better enable me to illustrate how the self is narrated in Kentridge’s work. I go on to show how medical scans provide him with a means to visualize the interior of the human form where the physical interior can come to stand for psychological states of which memory is a key component. I thus consider how Kentridge can be seen to view the interior of the body as a site for memory and briefly touch on current medical findings that suggest that memories are not only stored in the brain but also in the cells of other body parts. I further examine how Kentridge uses the analogy between landscape and memory to create a form of autobiographical and personal documentary and consider how his drawing process can be regarded as a form of self narration by way of its capturing of the passing of time and its speaking of how an image is made autobiographical. I finally discuss my own practical work which similarly explores how the self might be narrated through medical imagery and in my chosen media: stop frame animation, painting and printmaking.